Respostas
respondido por:
0
Resposta:
a) -7 + 6 - 1 = -2
b) -2 - 12 - 1 = -15
c) 12 - 7 + 23 = 28
d) (+18) + (+25) = 43
e) (-18) + (-5) = -23
f) (-13) + (+9) = -4
respondido por:
0
Resposta:
Explicação passo-a-passo:
Prestar atenção nos sinais de - na frente dos parênteses!
a) -7 + 6 - 1 = -2
b) -2 - 12 - 1 = -15
c) 12 - 7 + 23 = 28
d) (+18) - (+25) = 18 - 25 = - 7
e) (-18) + (-5) = -18 -5 = - 23
f) (-13) + (+9) = -13 +9 = - 4
Perguntas similares
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás